A Detailed Review for Predicting the Quantity of Sugar From Sugarcane Using Various Models - Kathirvel Narayanasamy; Ilayaraja Venkatachalam (IEEE Access)
The production of jaggery and white sugar is an essential aspect of the sugarcane industry. This review aims to assess a variety of techniques for estimating sugar content in sugarcane, including laboratory methods, formula calculations, device-based measurements, and machine-learning algorithms. This review aims to analyze various aspects of sugar production, including sugar prediction, processing techniques, and sugarcane quality parameters, and focuses on the use of sugarcane juice parameters to construct predictive models. Predicting the sugar content in sugarcane is crucial for optimizing agricultural practices, harvesting schedules, and processing operations in the sugar industry, including jaggery and white sugar production. Researchers have explored several methodologies and techniques for accurately predicting the sugar content of sugarcane prior to harvesting. The present analysis highlights that conventional regression algorithms can predict sugar content;however, multicollinearity restricts their effectiveness. To improve prediction accuracy and overcome existing limitations, future research should concentrate on developing advanced models that mitigate multicollinearity. In the existing research, it is difficult for users to comprehend the output of sugar prediction values. In the sugar industry, buyers and sellers typically measure sugarcane in metric tons, whereas sugar manufacturers typically measure sugar in kilograms. Therefore, it is necessary to analyze sugarcane juice parameters and develop a machine-learning model based on these data. Enhanced machine learning techniques and comprehensive quality parameters have the potential to significantly enhance the precision of sugar content predictions.